Self-Equilibrium Geometry of the Class-Theta Tetrahedral Tensegrity Module - BIENIEK, Zbigniew Wojciech (Engineering Transactions, 2016)
Tensegrity structures are mechanically stable because of the way in which they balance and distribute the mechanical stress, which is not principally a result of the strength of the individual components. This category of structures has the property that, even before the application of any external load, the members of the structure are already in tension or compression, that is, they are prestressed. There are different methods to find the equilibrium state attained by a tensegrity system for a given connectivity of the constituent cables and bars. In this paper, the tensegrity tetrahedron, characteristically shaped and free-standing, i.e., with no external loads, is investigated.